THE FACTORS AFFECTING DIVIDEND POLICY OF MANUFACTURING COMPANIES IN INDONESIA STOCK EXCHANGE - Berna Ratna Sari Napitupulu; Atik Djajanti (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Dividends as returns on investment in company shares are expected to increase investor wealth. Companies are not required to pay dividends every year but shareholders value stocks that pay dividends regularly. The purpose of this study is to analyze dividend policy in manufacturing companies listed on the Indonesian stock exchange. We analyze the relationship between company dividend policy and various determinant variables which are variables used as company life cycle, profitability, capital structure, liquidity, company assets, and institutional share ownership. By using data panel analysis and multivariate regression analysis, we process financial statement data for the period 2014-2016. We find that profitability, capital structure and assets have a significant effect on dividends while other variables have no effect. This research provides additional empirical evidence that explains the theory of life cycles in growth level and signaling explanation. Keywords: dividend payout, life cycle, profitability, capital structure, firm’s characteristics